Diurnal activity and energy budgets of Goosander Mergus merganser wintering on Chew Valley Lake, North Somerset: influence of time of day and sex - Newson, Stuart E; Hughes, Baz (Wildfowl, 1998)
Diurnal activity of wintering Goosander was studied at Chew Valley Lake using instantaneous scan sampling. The sex ratio of 0.48 males per female was relatively consistent through midwinter 1995/1996. Daily energy expenditure calculations, based upon published basal metabolic rates, suggested that feeding activities incurred the second highest energy cost after resting although feeding occurred for only a small proportion of daylight hour (14% for males and 17% females). Males devoted less time to feeding activities than females, although theoretically males need more energy per day, due to their larger size. It was calculated that males need between 175.5 and 216.6 g/fish/hr spent feeding, compared to females requiring between 117.2 and 144.6 g/fish/hr spent feeding. Males are therefore either more efficient at energy conservation or foraging (e.g. taking larger fish with higher calorific value). Assuming an assimilation efficiency of 80% and the food to have an energy content of 4.0 KJ/g, it was calculated that Goosander at Chew Valley Lake consumed about 10-13% of their body mass in fish per day.